Analisis Usability Aplikasi Perangkat Bergerak Jual Beli Online dengan Model People At The Center of Mobile Application Development (PACMAD) (Studi Kasus : Tokopedia, Bukalapak dan Shopee) - Nafilah Fauzi; Hanifah Muslimah Az-Zahra; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The existence of e-commerce mobile applications, makes it easier for online buying and selling transactions. About 95% of buyers review a product or service via cellphone. Shopee leads as the number one popular application on the Google AppStore in the free and shopping category, followed by Tokopedia in second place and Bukalapak in the 4th rank. This research is intended to find out whether application users choose applications based on usability or other factors. People At The Center of Mobile Application Development (PACMAD) usability model identified 7 attributes that reflect the usefulness of applications: effectiveness, efficiency, satisfaction, learnability, memorability, errors and cognitive load. The PACMAD method is considered suitable for solving problems with sentiments of review of mobile application users. The achievement of usability values ​​obtained by Tokopedia, Bukalapak and Shopee experienced a flat increase in the efficiency aspect. Only Bukalapak's aspects of effectiveness have increased, while Tokopedia and Shopee have decreased. Learnability aspects produce values ​​that are in line with aspects of effectiveness. The value of the memorability aspect is obtained in line with the combination of the comparison of effectiveness and efficiency values. Shopee got result of SUS Score at 73.75, while the Tokopedia performance score is 65.83 and Bukalapak is 67.92. Shopee got NASA-RTLX score at 8.2 followed by Tokopedia at 6.69 and Bukalapak with at 5.35 for the assessment of cognitive load aspects which indicate the severity of the demand for application use.